Food and animal welfare - Buller, Henry; Roe, Emma (Contemporary food studies, 2018)
Drawing together the latest research and a range of case studies, Henry Buller and Emma Roe guide readers on a fascinating journey through animal welfare issues 'from farm to fork'. Animal welfare offers a vital lens through which to explore the economies, culture and politics of food. This is the first text to provide a much-needed overview of this strongly debated area of the food industry.Buller and Roe explore how animal welfare is defined, advocated, assessed and implemented by farmers, veterinarians, distributors, and consumers. From the practicalities and limitations of establishing a basic standard of care for livestock, to the ethics of selling welfare as a product in the supermarket, this indispensable book offers empirical insights into a key aspect of the global food system: the lives, deaths, and consumption of animals which are at the core of the food chain. It is a must-read for students and scholars of animal welfare, agro-food studies and human-animal relations in disciplines such as geography, politics, anthropology, and sociology as well as animal behaviour, psychology and veterinary science.